Estimates for the best asymmetric approximations of asymmetric classes of functions - Motornyi, V. P.; Pas'ko, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Asymptotically sharp estimates are obtained for the best $(α, β)$ -approximations of the classes $W^r_{1; γ, δ}$ with natural $r$ by algebraic polynomials in the mean.